Acupotomy combined with massage for cervical spondylotic radiculopathy: A protocol for systematic review and meta-analysis. Issue 32 (7th August 2020) - Dai, Wenkang; Wang, Xiongwei; Xie, Rui; Zhuang, Minghui; Chang, Xiaojuan; Jin, Zhefeng; Yin, He; Feng, Minshan; Wei, Xu; Yu, Jie; Zhu, Liguo
Abstract: Background: Cervical spondylotic radiculopathy (CSR) is a clinical syndrome of radial neck and shoulder pain. Both Massage and Acupotomy have been widely used in the treatment of CSR, in China and achieved satisfied efficacy. Therefore, the aim of this study is to systematically evaluate the clinical efficacy of acupotomy combined with massage in the treatment of CSR. Methods: The following electronic databases will be searched: PubMed, Web of Science, the Cochrane Central Register of Controlled Trials (CENTRAL), the Cochrane Library, Embase, SinoMed, Clinical Trials. gov, the China National Knowledge Infrastructure (CNKI), Wanfang database, and VIP database. Two review authors independently search databases from their respective inception dates to September 2019 to identify potentially eligible studies. Cochrane Handbook 5.1 risk of bias assessment tool will be used to evaluate the methodological quality of the included studies. The Review Manager 5.3 will be used for all statistical analysis of the final included study. Results: The results of this systematic review and meta-analysis will provide a synthesis of existing evidences for the treatment of acupotomy combined with massage on CSR, especially in improving visual analog scale and symptom score. Conclusion: This study will summarize the current evidence of acupotomy combined with massage for the treatment of CSR. This study can further guide the promotion and clinical decisions. Ethics and dissemination: Ethical approval and patient consent are not required because this study is a literature-based study. This systematic review and meta-analysis will be published in a peer-reviewed journal. PROSPERO registration number: CRD42020171825.